2019
DOI: 10.1111/tri.13544
|View full text |Cite
|
Sign up to set email alerts
|

Total lymphoid irradiation in progressive bronchiolitis obliterans syndrome after lung transplantation: a single‐center experience and review of literature

Abstract: Limited results about treatment with total lymphoid irradiation (TLI) in lung transplant (LTx) recipients suffering from progressive bronchiolitis obliterans syndrome (BOS) have been reported. We performed a retrospective analysis of all LTx recipients undergoing TLI for progressive BOS in our center, focusing on long-term outcomes regarding overall survival and lung allograft function. Treatment with TLI (2004-2017, n = 20, 1 BOS stage 1, 6 BOS stage 2, and 13 BOS stage 3) resulted in significant attenuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…analyzed 16 cases of BOS treated with TLI and observed a significant monthly attenuation in FEV 1 decline from 246 ± 171 ml/month to 64 ± 171 ml/month 3 months before and after TLI (p = .0008) and 197 ± 116 ml/month versus 59 ± 91 ml/month 6 months before and after TLI (p = .002). 12 Likewise, Diamond et al observed a stop in FEV 1 decline after TLI in four rapid decliner patients who experienced a 40% decrease in FEV 1 3 months before the treatment. 13 Fisher et al…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…analyzed 16 cases of BOS treated with TLI and observed a significant monthly attenuation in FEV 1 decline from 246 ± 171 ml/month to 64 ± 171 ml/month 3 months before and after TLI (p = .0008) and 197 ± 116 ml/month versus 59 ± 91 ml/month 6 months before and after TLI (p = .002). 12 Likewise, Diamond et al observed a stop in FEV 1 decline after TLI in four rapid decliner patients who experienced a 40% decrease in FEV 1 3 months before the treatment. 13 Fisher et al…”
Section: Discussionmentioning
confidence: 92%
“…Slow decline was defined as an average monthly rate of FEV 1 decline <100 ml/mo, and rapid decline as an FEV 1 decline ≥100 ml/mo, both measured over 3 months prior to TLI. 12,13 Performance status was assessed using the Karnofsky Performance Status (KPS) prior to the start of the TLI. Subsequently, the patients were divided into groups with KPS >70 or ≤70.…”
Section: Methodsmentioning
confidence: 99%
“…Those who completed treatment had a decrease in rate of FEV 1 decline that was durable (65). Subsequent series show a similar stabilization in the rate of FEV 1 decline (66)(67)(68). However, leukopenia and infections are common side-effects of TLI (65,66).…”
Section: Total Lymphoid Irradiationmentioning
confidence: 90%
“…Alemtuzumab has been used for CLAD, with retrospective data demonstrating promise for stabilization of lung function, and ATG has been shown to demonstrate improved lung function in 40% of patients in one retrospective review, albeit with a high rate of serious adverse effects, including serum sickness, cytokine release syndrome, and infection (145,(169)(170)(171). ECP, TLI and retransplantation can also be considered for these patients (169,(172)(173)(174)(175)(176)(177)(178)(179)(180).…”
Section: Rejectionmentioning
confidence: 99%